THE PLACE AND ROLE OF TRANSVERSAL KEY COMPETENCES IN VOCATIONAL EDUCATION AND TRAINING IN THE CONTEXT OF LIFE-LONG LEARNING - Zeiberte, Livija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Vocational education and training (VET) plays a central role in the lifelong learning (LLL) continuum. In Europe Union and in Latvia, LLL is recognized and accepted as a tool that promotes human entrepreneurship, employability and resilience, active civic participation, social inclusion and personal self-development. The COVID-19 pandemic has seriously disrupted standard education and training activities, including VET across Europe. Young people entering the workforce at this time will find it harder to secure their first job. VET have to provide people with skills and competences for work which help them to cope with emergency situations and economic shocks and get or create jobs in demand on the labour market. Transversal key competences (TKC) is an essential part of VET. Professional and general competences reflect an individual's ability to work in a specific context, i.e. professional environment; at the same time they presume a set of abilities which we call transversal. The aim of this research is to analyze the process of implementation of  four TKC (learning to learn, social and civic competences, initiative-taking and entrepreneurship, and cultural awareness and expression) in VET curriculum in Latvia. It is part of wider study of the National Centre for Education of Latvia and Erasmus + Srategic Partnership project Developing, assessing and validating transversal key competences in the formal initial and continuing vocational education and training (TRACK-VET), (2017–2020). The project produce detailed analysis of the systemic solutions, practices, and techniques in six EU countries regarding development and assessment of TKC.